The genus Milnesium (Eutardigrada: Milnesiidae) in the Sierra Nevada de Santa Marta (Colombia), with the description of Milnesium kogui sp. nov. - Londoño, Rosana; Daza, Anisbeth; Caicedo, Martín; Quiroga, Sigmer; Kaczmarek, Łukasz (Zootaxa, 2015)
A new species, Milnesium kogui sp. nov. is described from the Sierra Nevada de Santa Marta, Colombia. The new species belongs to the tardigradum group and is most similar, by the claw configuration [2-2]-[2-2], to Milnesium dujiangensis and Milnesium katarzynae. Milnesium kogui sp. nov. differs from M. dujiangensis mainly by the presence of primary branches on all legs and from M. katarzynae by the absence of dorsal sculpture. Additionally, in this paper we present a list of all Milnesium species recorded in Colombia including Milnesium cf. barbadosense Meyer & Hinton, 2012 and M. brachyungue Binda & Pilato, 1990, new additions to the recorded fauna of Colombia.